Development of Integrated 3-Dimensional Computer Graphics Human Head Model. Issue 6 (2nd March 2021) - Kiyofuji, Satoshi; Kin, Taichi; Kakizawa, Yukinari; Doke, Takehito; Masuda, Taisuke; Yamashita, Juli; Shono, Naoyuki; Nakatomi, Hirofumi; Morita, Akio; Harada, Kanako; Saito, Nobuhito
Abstract: BACKGROUND: Understanding the complex anatomy of neurostructures is very important in various stages of medical education, from medical students to experienced neurosurgeons, and, ultimately, for the knowledge of human beings. OBJECTIVE: To develop an interactive computer graphics (CG) anatomic head model and present the current progress. METHODS: Based on the prior head 3-dimensional CG (3DCG) polygon model, 23 additional published papers and textbooks were consulted, and 2 neurosurgeons and 1 CG technician performed revision and additional polygon modeling. Three independent neurosurgeons scored the clear visibility of anatomic structures relevant to neurosurgical procedures (anterior petrosal and supracerebellar infratentorial approaches) in the integrated 3DCG model (i model) and patients' radiological images (PRIs) such as those obtained from computed tomography, magnetic resonance imaging, and angiography. RESULTS: The i model consisted of 1155 parts (.stl format), with a total of 313 763 375 polygons, including 10 times more information than the foundation model. The i model was able to illustrate complex and minute neuroanatomic structures that PRIs could not as well as extracranial structures such as paranasal sinuses. Our subjective analysis showed that the i model had better clear visibility scores than PRIs, particularly in minute nerves, vasculatures, and dural structures. CONCLUSION: The i model more clearly illustrates minute anatomic structures than PRIs and uniquely illustrates nuclei and fibers that radiological images do not. The i model complements cadaveric dissection by increasing accessibility according to spatial, financial, ethical, and social aspects and can contribute to future medical education.